Genomic Analysis of Carbapenem-Resistant Acinetobacter baumannii Isolated from Bloodstream Infections in South Korea - Wook Jong Jeon; Yoo Jung Kim; Ju Hui Seo; Jung Sik Yoo; Dong Chan Moon (Antibiotics)
Background/Objectives: Bloodstream infection by carbapenem-resistant Acinetobacter baumannii (CRAB) is a serious clinical problem worldwide. To study its clonal relationship and genetic features, we report the draft genome sequence of CRAB strains isolated from human blood in South Korea. Methods: Among A. baumannii strains isolated from patients at nine general hospitals in 2020, 12 CRAB strains of different genotypes were selected. Genomic DNA was sequenced using a combination of Illumina MiSeq and Oxford Nanopore MinION platforms. Antimicrobial susceptibility testing was performed using the disk diffusion method. Antimicrobial resistance and virulence genes were investigated in silico using the Center for Genomic Epidemiology server and the Virulence Factors Database. Results: The multilocus sequence types of isolates included ST191, ST195, ST357, ST369, ST451, ST469, ST491, ST784, ST862, ST1933, ST2929, and a novel type, ST3326. The predominant sequence type, ST191, demonstrated close genetic relationships with several isolates, including ST469, ST369, ST195, ST784, ST491, and ST3326, with ST3326 classified as a subgroup of ST191. We found 18 antimicrobial resistance genes and one quaternary ammonium compound resistance gene. All examined strains harbored blaOXA-23, which is associated with carbapenem resistance. While variations in antibiotic and disinfectant resistance genes were observed, all isolates exhibited similar virulence factors, with the exception of the biofilm and capsule production genes. Conclusions: This nationwide report of the draft genome sequence of patient-derived strains provides valuable insights into the genomic features associated with clonal relationships and antimicrobial resistance of CRAB in bloodstream infections.